A high-entropy alloy oxide, a preparation method and application thereof
Patent Information
- Application Number
- CN202310344460.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-03
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2043-04-03
AI Technical Summary
然而,Ru在酸性析氧反应条件下存在稳定性较差的问题,这主要是由于Ru基氧化物中晶格氧参与反应程度较大,导致了催化剂结构的破坏
[0073] (1) The pentagonal high-entropy alloy oxide provided by the present invention has a low degree of lattice oxygen participation in the oxygen evolution reaction, exhibiting better electrochemical stability of the acidic oxygen evolution reaction, and has the advantages of low cost and good catalytic stability.
Smart Images

Figure CN116334662B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of catalyst technology, and in particular to a high-entropy alloy oxide, its preparation method, and its application. Background Technology
[0002] The utilization of renewable energy sources such as solar, wind, and tidal energy is an important way to solve energy and environmental problems. However, the intermittent nature of renewable energy power generation can impact the power grid and thus affect its sustainable utilization.
[0003] Proton exchange membrane electrolysis (PEMWE) technology boasts advantages such as high current density and high power density, enabling the use of electricity generated from renewable energy sources for hydrogen production through water electrolysis, thus achieving the conversion and sustainable utilization of renewable energy. However, the oxygen evolution reaction at the anode in water electrolysis involves a four-electron-proton transfer process, exhibiting slow reaction kinetics and requiring the use of large quantities of iridium-based catalysts. However, the low abundance of iridium in the Earth's crust and its prohibitively high cost severely limit the practical application of PEMWE technology. Therefore, developing low-cost, highly stable anodic oxygen evolution reaction catalysts is crucial for reducing the cost of PEMWE technology and realizing its large-scale application.
[0004] Ru-based materials have attracted widespread attention due to their lower cost and higher intrinsic activity compared to Ir-based catalysts. However, Ru exhibits poor stability under acidic oxygen evolution reaction conditions, primarily because the lattice oxygen in Ru-based oxides participates significantly in the reaction, leading to catalyst structure degradation. Therefore, suppressing the participation of lattice oxygen in Ru-based oxides to ensure good stability remains a pressing technical problem to be solved. Summary of the Invention
[0005] In view of this, the technical problem to be solved by the present invention is to provide a high-entropy alloy oxide, its preparation method and application. The high-entropy alloy oxide provided by the present invention exhibits superior catalytic activity and electrochemical stability in acidic oxygen evolution reaction.
[0006] This invention provides a high-entropy alloy oxide, which includes five metallic elements: Ti, Nb, Hf, W, and Ru.
[0007] Preferably, the molar fraction of Ru in the high-entropy alloy oxide is 40% to 60%.
[0008] This invention also provides a method for preparing high-entropy alloy oxides, comprising the following steps:
[0009] A) A suspension is obtained by mixing a liquid containing tungsten salt, a titanium salt solution, a niobium salt solution, a hafnium salt solution, a ruthenium salt solution, and a zinc nitrate solution;
[0010] B) The suspension was mixed with nitrate and then subjected to rotary evaporation to obtain a catalyst precursor;
[0011] C) The catalyst precursor is calcined in air at 400°C to 500°C to obtain a high-entropy alloy oxide.
[0012] Preferably, in step A), the tungsten salt comprises ammonium tungstate and / or sodium tungstate;
[0013] The titanium salt includes potassium dioxalate titanate;
[0014] The niobium salt includes ammonium oxalate niobate;
[0015] The hafnium salt includes hafnium tetrachloride;
[0016] The ruthenium salt includes ruthenium chloride.
[0017] Preferably, in step A), the molar ratio of the tungsten salt, titanium salt, niobium salt, hafnium salt, and ruthenium salt is 0.1~0.15:0.1~0.15:0.1~0.15:0.1~0.15:0.4~0.6.
[0018] The molar ratio of zinc nitrate to ruthenium salt is 0.04~0.06:0.4~0.6.
[0019] Preferably, in step B), the nitrate is sodium nitrate;
[0020] The molar ratio of the nitrate to the ruthenium salt is 16~21:0.4~0.6.
[0021] Preferably, in step B), the stirring speed is 300~800 rpm;
[0022] The temperature of the rotary evaporation is 50~80℃.
[0023] Preferably, in step C), the calcination time is 0.3 to 0.7 h.
[0024] Preferably, in step C), after calcination, the process further includes: acid washing;
[0025] The pickling includes: ultrasonic dispersion washing with acid solution;
[0026] The acid solution includes hydrochloric acid solution or sulfuric acid solution;
[0027] The process after acid washing also includes: filtration and drying.
[0028] This invention also provides an application of the high-entropy alloy oxide described above or the high-entropy alloy oxide prepared by the preparation method described above as an anode catalyst for proton exchange membrane water electrolysis.
[0029] This invention provides a high-entropy alloy oxide, which is a Ru-based pentagonal high-entropy alloy oxide comprising five metallic elements: Ti, Nb, Hf, W, and Ru. The pentagonal high-entropy alloy oxide provided by this invention exhibits a relatively large energy barrier for atomic diffusion and migration due to the influence of lattice disorder. It demonstrates low lattice oxygen participation in the oxygen evolution reaction and exhibits superior catalytic activity and electrochemical stability in acidic oxygen evolution reactions. It possesses advantages such as low cost and good catalytic stability, making it suitable as an anode catalyst for proton exchange membrane water electrolysis. Furthermore, the preparation method of the pentagonal high-entropy alloy oxide catalyst provided by this invention is simple, has a short preparation process, and is environmentally friendly. Attached Figure Description
[0030] Figure 1 The TiNbHfWRuO of Embodiment 1 of the present invention x SEM images of high-entropy alloy oxides;
[0031] Figure 2 The TiNbHfWRuO of Embodiment 1 of the present invention x TEM image of high-entropy alloy oxides;
[0032] Figure 3 The TiNbHfWRuO of Embodiment 1 of the present invention x EDS elemental mapping diagram of high-entropy alloy oxides;
[0033] Figure 4 The TiNbHfWRuO of Embodiment 1 of the present invention x XRD pattern of high-entropy alloy oxides;
[0034] Figure 5 The TiNbHfWRuO of Embodiment 1 of the present invention x Linear sweep voltammetric curves of high-entropy alloy oxides in 0.5 mol / L sulfuric acid solution;
[0035] Figure 6 The TiNbHfWRuO of Embodiment 1 of the present invention x High-entropy alloy oxides in 0.5 mol / L sulfuric acid solution have an A / cm ratio of 10 mA / cm. 2 Timing potential curves at current density. Detailed Implementation
[0036] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0037] This invention provides a high-entropy alloy oxide, which is a Ru-based pentagonal high-entropy alloy oxide, a homogeneous phase oxide comprising five metallic elements: Ti, Nb, Hf, W, and Ru. In this high-entropy alloy oxide, each metal exists in an oxidized state.
[0038] In some embodiments of the present invention, the molar fraction of Ru in the high-entropy alloy oxide is 40% to 60%; specifically 43%, 45%, 51% or 41%.
[0039] In some embodiments of the present invention, the high-entropy alloy oxide exhibits a nanocluster morphology composed of grains and possesses a stacked pore structure. The nanoparticles in the high-entropy alloy oxide are relatively uniformly dispersed and of uniform size.
[0040] In some embodiments of the present invention, the high-entropy alloy oxide has a composition of Ti. 23 Nb9Hf 13 W 12 Ru 43 O x Ti 21 Nb9Hf 13 W 12 Ru 45 O x Ti 19 Nb8Hf 11 W 11 Ru 51 O x or Ti 24 Nb 10 Hf 12 W 13 Ru 41 O x The range of x is 100~200.
[0041] This invention also provides a method for preparing the high-entropy alloy oxide described above, comprising the following steps:
[0042] A) A suspension is obtained by mixing a liquid containing tungsten salt, a titanium salt solution, a niobium salt solution, a hafnium salt solution, a ruthenium salt solution, and a zinc nitrate solution;
[0043] B) The suspension was mixed with nitrate and then subjected to rotary evaporation to obtain a catalyst precursor;
[0044] C) The catalyst precursor is calcined in air at 400°C to 500°C to obtain a high-entropy alloy oxide.
[0045] In step A):
[0046] A suspension is obtained by mixing a liquid containing tungsten salt, a titanium salt solution, a niobium salt solution, a hafnium salt solution, a ruthenium salt solution, and a zinc nitrate solution.
[0047] In some embodiments of the present invention, the tungsten salt-containing liquid is obtained by mixing tungsten salt with water. The mixing can be carried out at room temperature. The tungsten salt is a water-soluble tungsten salt, specifically including ammonium tungstate and / or sodium tungstate. In some embodiments, the ratio of tungsten salt to water is 1 mg:1 mL.
[0048] In some embodiments of the present invention, the titanium salt solution is obtained by ultrasonically dispersing and dissolving a titanium salt in water. The titanium salt comprises potassium dioxalate titanate. The concentration of the titanium salt solution is 8-12 mg / mL; specifically, 10 mg / mL.
[0049] The niobium salt solution is obtained by ultrasonically dispersing and dissolving niobium salt in water. The niobium salt includes ammonium oxalate niobate. The concentration of the niobium salt solution is 8-12 mg / mL; specifically 10 mg / mL.
[0050] The hafnium salt solution is obtained by ultrasonically dispersing and dissolving hafnium salt in water. The hafnium salt includes hafnium tetrachloride. The concentration of the hafnium salt solution is 8-12 mg / mL; specifically 10 mg / mL.
[0051] The ruthenium salt solution is obtained by ultrasonically dispersing and dissolving ruthenium salt in water. The ruthenium salt includes ruthenium chloride. The concentration of the ruthenium salt solution is 8~12 mg / mL; specifically 10 mg / mL.
[0052] In some embodiments of the present invention, the molar ratio of the tungsten salt, titanium salt, niobium salt, hafnium salt, and ruthenium salt is 0.1~0.15:0.1~0.15:0.1~0.15:0.4~0.6; specifically 0.1:0.1:0.1:0.1:0.43 or 0.15:0.15:0.15:0.15:0.47.
[0053] In this invention, the role of zinc nitrate is to form zinc oxide during the preparation process to occupy part of the position, and to wash away the porous structure during the pickling process.
[0054] In some embodiments of the present invention, the solvent for the zinc nitrate solution is water. The concentration of the zinc nitrate solution is 8-12 mg / mL; specifically, 10 mg / mL.
[0055] The molar ratio of zinc nitrate to ruthenium salt is 0.04~0.06:0.4~0.6; specifically 0.06:0.52 and 0.04:0.44.
[0056] In step B):
[0057] The suspension was mixed with nitrate and then rotary evaporated to obtain the catalyst precursor.
[0058] In some embodiments of the present invention, the nitrate is sodium nitrate.
[0059] The molar ratio of the nitrate to the ruthenium salt is 16~21:0.4~0.6; specifically 19.38:0.52, 20.16:0.52, and 19.38:0.44.
[0060] In this invention, the addition of nitrate has two functions: first, it allows the added nitrate to melt during the high-temperature roasting process (subsequent calcination process), providing a molten salt environment during roasting, which helps to achieve uniform mixing of the components in the catalyst precursor; second, the introduction of nitrate can act as an oxidizing agent, which is beneficial to the formation of alloy oxides.
[0061] In some embodiments of the present invention, the mixing process further includes stirring for 2 to 4 hours, specifically 3 hours.
[0062] The stirring speed is 300~800 rpm; specifically 500 rpm.
[0063] In some embodiments of the present invention, the temperature of the rotary evaporation is 50~80°C; specifically 60°C; and the rotary evaporation is carried out under water bath conditions.
[0064] In step C):
[0065] The catalyst precursor was calcined in air at 400°C to 500°C to obtain a high-entropy alloy oxide.
[0066] In some embodiments of the present invention, the calcination temperature is 400°C or 450°C; the calcination time is 0.3 to 0.7 h; specifically 0.5 h.
[0067] In some embodiments of the present invention, the calcination process further includes acid washing.
[0068] The acid washing includes ultrasonic dispersion washing with an acid solution. The acid solution includes a hydrochloric acid solution or a sulfuric acid solution, wherein the concentration of the hydrochloric acid solution is 1 mol / L and the concentration of the sulfuric acid solution is 0.5 mol / L. In some embodiments, the volume of the acid solution used is 35-45 mL.
[0069] The process after acid washing also includes: filtration and drying.
[0070] The method for preparing high-entropy alloy oxides provided by this invention is a direct air-atmosphere calcination method assisted by nitrate melting, which forms a uniform high-entropy alloy oxide phase with uniform element distribution of five elements: Ti, Nb, Hf, W, and Ru.
[0071] This invention also provides an application of the high-entropy alloy oxide described above, or the high-entropy alloy oxide prepared by the method described above, as a catalyst. Specifically, it is used as an anode catalyst for proton exchange membrane water electrolysis. It features low cost, high catalytic activity, and good stability.
[0072] The beneficial effects of this invention are:
[0073] (1) The pentagonal high-entropy alloy oxide provided by the present invention has a low degree of lattice oxygen participation in the oxygen evolution reaction, exhibiting better electrochemical stability of the acidic oxygen evolution reaction, and has the advantages of low cost and good catalytic stability.
[0074] (2) The preparation method of the pentagonal high-entropy alloy oxide provided by the present invention is simple, has a short preparation process, and is environmentally friendly.
[0075] The present invention does not impose any special restrictions on the source of the raw materials used above, and they can be commercially available.
[0076] To further illustrate the present invention, the following detailed description of a high-entropy alloy oxide, its preparation method, and its application, in conjunction with embodiments, is provided by the present invention, but should not be construed as limiting the scope of protection of the present invention.
[0077] All raw materials used in the examples were of analytical grade.
[0078] Example 1
[0079] Methods for preparing high-entropy alloy oxides include:
[0080] 1) At room temperature, 17 mg (0.06 mmol) of ammonium tungstate was dissolved in 17 mL of deionized water to obtain a liquid containing tungsten salt;
[0081] 0.06 mmol of potassium bis(oxalate) titanate was ultrasonically dispersed and dissolved in water to obtain a 10 mg / mL potassium bis(oxalate) titanate solution; 0.06 mmol of ammonium niobate oxalate was ultrasonically dispersed and dissolved in water to obtain a 10 mg / mL ammonium niobate oxalate solution; 0.06 mmol of hafnium tetrachloride was ultrasonically dispersed and dissolved in water to obtain a 10 mg / mL hafnium tetrachloride solution; 0.26 mmol of ruthenium chloride was ultrasonically dispersed and dissolved in water to obtain a 10 mg / mL ruthenium chloride solution; and 0.03 mmol of zinc nitrate was dissolved in water to obtain a 10 mg / mL zinc nitrate solution.
[0082] The tungsten salt-containing liquid, potassium dioxamate titanate solution, ammonium niobate oxalate solution, hafnium tetrachloride solution, ruthenium chloride solution, and zinc nitrate solution are mixed to obtain a suspension.
[0083] 2) The suspension was mixed with 9.69 mmol sodium nitrate and stirred at 500 rpm for 3 h. The catalyst precursor was obtained by rotary evaporation under a 60°C water bath.
[0084] 3) The catalyst precursor was calcined at 400°C for 0.5 h in air, washed with 35 mL of 1 mol / L hydrochloric acid solution, filtered, and dried to obtain TiNbHfWRuO x High-entropy alloy oxide. The molar fraction of Ru is 43%.
[0085] For TiNbHfWRuO of Example 1 x SEM analysis of high-entropy alloy oxides yielded the following results: Figure 1 As shown. Figure 1 The TiNbHfWRuO of Embodiment 1 of the present invention x SEM images of high-entropy alloy oxides. From Figure 1 It can be seen that the high-entropy alloy oxide exhibits a nanocluster morphology composed of grains and has a stacked pore structure.
[0086] For TiNbHfWRuO of Example 1 x TEM analysis of high-entropy alloy oxides yielded the following results: Figure 2 As shown. Figure 2 The TiNbHfWRuO of Embodiment 1 of the present invention x TEM image of high-entropy alloy oxides. From Figure 2 It can be seen that the nanoparticles in the high-entropy alloy oxide are relatively uniformly dispersed and have uniform size.
[0087] For TiNbHfWRuO of Example 1 x EDS elemental mapping image analysis was performed on high-entropy alloy oxides, and the results are as follows: Figure 3 As shown. Figure 3 The TiNbHfWRuO of Embodiment 1 of the present invention x EDS elemental mapping diagram of high-entropy alloy oxides. From Figure 3 It can be seen that the obtained TiNbHfWRuO x The high-entropy alloy oxide exhibits a uniform distribution of Ti, Nb, Hf, W, Ru, and O elements, without forming a phase-separated structure. ICP testing indicates that the high-entropy alloy oxide is composed primarily of Ti. 23 Nb9Hf 13 W 12 Ru 43 O x (x ranges from 100 to 200).
[0088] For TiNbHfWRuO of Example 1x X-ray diffraction analysis of high-entropy alloy oxides yielded the following results: Figure 4 As shown. Figure 4 The TiNbHfWRuO of Embodiment 1 of the present invention x XRD patterns of high-entropy alloy oxides. From Figure 4 It can be seen that the shape of the diffraction peak corresponds to a single RuO2 diffraction peak, the position of the diffraction peak is slightly shifted, no other metal oxide diffraction peaks were found, and no phase separation structure was formed.
[0089] TiNbHfWRuO from Example 1 x Linear sweep voltammetry was performed on high-entropy alloy oxides in 0.5 mol / L sulfuric acid solution, and the results are as follows: Figure 5 As shown. Figure 5 The TiNbHfWRuO of Embodiment 1 of the present invention x Linear sweep voltammetry curves of high-entropy alloy oxides in 0.5 mol / L sulfuric acid solution. From... Figure 5 It can be seen that the TiNbHfWRuO x High-entropy alloy oxides at a current density of 10 mA / cm 2 The overpotential is low, at 251 mV, exhibiting superior activity compared to commercial RuO2 catalysts.
[0090] For TiNbHfWRuO of Example 1 x High-entropy alloy oxides in 0.5 mol / L sulfuric acid solution at 10 mA / cm 2 Chronopotential testing was performed at current density, and the results are as follows: Figure 6 As shown. Figure 6 The TiNbHfWRuO of Embodiment 1 of the present invention x High-entropy alloy oxides in 0.5 mol / L sulfuric acid solution at 10 mA / cm 2 Timothy potential curves at current density. From Figure 6 It can be seen that the TiNbHfWRuO x During a 25-h chronopotential test, the high-entropy alloy oxide showed no significant activity decay as its potential increased from 1.51 V to 1.57 V, demonstrating superior stability compared to commercial RuO2 catalysts.
[0091] Example 2
[0092] The difference from Example 1 is as follows:
[0093] In step 3), the calcination temperature is 450℃;
[0094] Finally, we obtain TiNbHfWRuO x In high-entropy alloy oxides, the molar fraction of Ru is 45%.
[0095] According to ICP testing, the composition of the high-entropy alloy oxide is Ti. 21 Nb9Hf 13 W 12 Ru 45 O x (x ranges from 100 to 200).
[0096] The TiNbHfWRuO prepared in Example 2 x Linear sweep voltammetry was performed on the high-entropy alloy oxide in 0.5 mol / L sulfuric acid solution. The results showed that the TiNbHfWRuO x High-entropy alloy oxides at a current density of 10 mA / cm 2 The overpotential was 255 mV, which showed better activity than commercial RuO2 catalysts.
[0097] For TiNbHfWRuO in Example 2 x High-entropy alloy oxides in 0.5 mol / L sulfuric acid solution at 10 mA / cm 2 Chronopotential testing was performed at current density, and the results showed that the TiNbHfWRuO x During a 25-h chronopotential test, the high-entropy alloy oxide showed no significant activity decay as its potential increased from 1.52 V to 1.59 V, demonstrating superior stability compared to commercial RuO2 catalysts.
[0098] Example 3
[0099] The difference from Example 1 is as follows:
[0100] In step 2):
[0101] The suspension was mixed with 10.08 mmol sodium nitrate and stirred at 700 rpm for 2 h. The catalyst precursor was obtained by rotary evaporation under a water bath at 60 °C.
[0102] Finally, we obtain TiNbHfWRuO x In the high-entropy alloy oxide, the molar fraction of Ru is 51%.
[0103] According to ICP testing, the composition of the high-entropy alloy oxide is Ti. 19 Nb8Hf 11 W 11 Ru 51 O x (x ranges from 100 to 200).
[0104] The TiNbHfWRuO prepared in Example 3 xLinear sweep voltammetry was performed on the high-entropy alloy oxide in 0.5 mol / L sulfuric acid solution. The results showed that the TiNbHfWRuO x High-entropy alloy oxides at a current density of 10 mA cm⁻¹ -2 The overpotential was 256 mV, which shows better activity than commercial RuO2 catalysts.
[0105] For TiNbHfWRuO in Example 3 x High-entropy alloy oxides in 0.5 mol / L sulfuric acid solution at 10 mA cm⁻¹ -2 Chronopotential testing was performed at current density, and the results showed that the TiNbHfWRuO x During a 25-h chronopotential test, the high-entropy alloy oxide showed no significant activity decay as its potential increased from 1.52 V to 1.60 V, demonstrating superior stability compared to commercial RuO2 catalysts.
[0106] Example 4
[0107] The difference from Example 1 is as follows:
[0108] In step 1):
[0109] At room temperature, 20 mg (0.07 mmol) of ammonium tungstate was dissolved in 20 mL of deionized water to obtain a liquid containing tungsten salt;
[0110] 0.07 mmol potassium bis(oxalate) titanate was ultrasonically dispersed and dissolved in water to obtain a 10 mg / mL potassium bis(oxalate) titanate solution; 0.07 mmol ammonium niobate oxalate was ultrasonically dispersed and dissolved in water to obtain a 10 mg / mL ammonium niobate oxalate solution; 0.07 mmol hafnium tetrachloride was ultrasonically dispersed and dissolved in water to obtain a 10 mg / mL hafnium tetrachloride solution; 0.22 mmol ruthenium chloride was ultrasonically dispersed and dissolved in water to obtain a 10 mg / mL ruthenium chloride solution; 0.02 mmol zinc nitrate was dissolved in water to obtain a 10 mg / mL zinc nitrate solution.
[0111] The tungsten salt-containing liquid, potassium dioxamate titanate solution, ammonium niobate oxalate solution, hafnium tetrachloride solution, ruthenium chloride solution, and zinc nitrate solution are mixed to obtain a suspension.
[0112] Finally, we obtain TiNbHfWRuO x In the high-entropy alloy oxide, the molar fraction of Ru is 41%.
[0113] According to ICP testing, the composition of the high-entropy alloy oxide is Ti. 24 Nb 10 Hf 12 W13 Ru 41 O x (x ranges from 100 to 200).
[0114] The TiNbHfWRuO prepared in Example 4 x Linear sweep voltammetry was performed on the high-entropy alloy oxide in 0.5 mol / L sulfuric acid solution. The results showed that the TiNbHfWRuO x High-entropy alloy oxides at a current density of 10 mA cm⁻¹ -2 The overpotential was 261 mV, which shows better activity than commercial RuO2 catalysts.
[0115] For TiNbHfWRuO in Example 4 x High-entropy alloy oxides in 0.5 mol / L sulfuric acid solution at 10 mA cm⁻¹ -2 Chronopotential testing was performed at current density, and the results showed that the TiNbHfWRuO x During a 25-h chronopotential test, the high-entropy alloy oxide showed no significant activity decay as its potential increased from 1.53 V to 1.61 V, demonstrating superior stability compared to commercial RuO2 catalysts.
[0116] Comparative Example 1
[0117] In Example 1 of this invention, an additional metallic element, Mo, is added to form a six-element high-entropy alloy oxide TiNbHfMoWRuO. x The addition of Mo ensures that the theoretical mole fraction of Ru remains unchanged.
[0118] According to ICP testing, the composition of the high-entropy alloy oxide is Ti. 14 Nb7Hf 12 Mo5W 11 Ru 51 O x (x ranges from 100 to 200).
[0119] Comparative Example 1: TiNbHfMoWRuO x The high-entropy alloy oxide was subjected to linear sweep voltammetry and chronopotential testing under the same conditions as in Example 1. The results show that the TiNbHfMoWRuO x High-entropy alloy oxides at a current density of 10 mA / cm 2 The overpotential was 246 mV, and during the approximately 19 h chronopotential test, the potential increased from 1.50 V to 2.0 V.
[0120] Comparative Example 2
[0121] In Embodiment 1 of the present invention, one metal element is removed to form TiNbHfRuO. x Quaternary alloy oxides ensure that the theoretical molar fraction of Ru doped remains unchanged after the removal of elements.
[0122] According to ICP testing, the composition of the high-entropy alloy oxide is Ti. 56 Nb 10 Hf 15 Ru 19 O x (x ranges from 100 to 200).
[0123] The TiNbHfRuO of Comparative Example 2 x The high-entropy alloy oxide was subjected to linear sweep voltammetry and chronopotential testing under the same conditions as in Example 1. The results show that the TiNbHfRuO x Alloy oxides at a current density of 10 mA / cm 2 The overpotential was 267 mV, and during the approximately 18-hour chronopotential test, the potential increased from 1.54 V to 2.0 V.
[0124] Comparative Example 3
[0125] In Embodiment 1 of the present invention, two metal elements are removed to form TiNbRuO. x Ternary alloy oxides ensure that the theoretical molar fraction of Ru doped remains unchanged after the removal of elements.
[0126] According to ICP testing, the composition of the high-entropy alloy oxide is Ti. 58 Nb 19 Ru 23 O x (x ranges from 100 to 200).
[0127] The TiNbRuO of Comparative Example 3 x The high-entropy alloy oxide was subjected to linear sweep voltammetry and chronopotential testing under the same conditions as in Example 1. The results show that the TiNbRuO x Alloy oxides at a current density of 10 mA / cm 2 The overpotential was 450 mV, and during the approximately 2-hour chronopotential test, the potential increased from 1.64 V to 2.0 V.
[0128] Experimental results show that the present invention achieves better data results by using specific elements and specific element doping amounts. The oxygen evolution reaction (OER) of higher-level high-entropy alloy oxides formed by the addition of excess elements or lower-level alloy oxides formed by the deletion of elements is poor.
[0129] The above description of the disclosed embodiments enables those skilled in the art to make or use the invention. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the invention. Therefore, the invention is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A high-entropy alloy oxide, said high-entropy alloy oxide comprising five metallic elements: Ti, Nb, Hf, W, and Ru; In the high-entropy alloy oxide, the molar fraction of Ru is 40%~60%; The preparation method of the high-entropy alloy oxide includes the following steps: A) A suspension is obtained by mixing a liquid containing tungsten salt, a titanium salt solution, a niobium salt solution, a hafnium salt solution, a ruthenium salt solution, and a zinc nitrate solution; The molar ratio of the tungsten salt, titanium salt, niobium salt, hafnium salt, and ruthenium salt is 0.1~0.15:0.1~0.15:0.1~0.15:0.1~0.15:0.4~0.6; B) The suspension was mixed with nitrate and then subjected to rotary evaporation to obtain a catalyst precursor; C) The catalyst precursor is calcined in air at 400°C to 500°C to obtain a high-entropy alloy oxide.
2. The method for preparing the high-entropy alloy oxide according to claim 1, comprising the following steps: A) A suspension is obtained by mixing a liquid containing tungsten salt, a titanium salt solution, a niobium salt solution, a hafnium salt solution, a ruthenium salt solution, and a zinc nitrate solution; B) The suspension was mixed with nitrate and then subjected to rotary evaporation to obtain a catalyst precursor; C) The catalyst precursor is calcined in air at 400°C to 500°C to obtain a high-entropy alloy oxide.
3. The preparation method according to claim 2, characterized in that, In step A), the tungsten salt includes ammonium tungstate and / or sodium tungstate; The titanium salt includes potassium dioxalate titanate; The niobium salt includes ammonium oxalate niobate; The hafnium salt includes hafnium tetrachloride; The ruthenium salt includes ruthenium chloride.
4. The preparation method according to claim 2, characterized in that, In step A), the molar ratio of zinc nitrate to ruthenium salt is 0.04~0.06:0.4~0.
6.
5. The preparation method according to claim 2, characterized in that, In step B), the nitrate is sodium nitrate; The molar ratio of the nitrate to the ruthenium salt is 16~21:0.4~0.
6.
6. The preparation method according to claim 2, characterized in that, In step B), the stirring speed is 300~800 rpm; The temperature of the rotary evaporation is 50~80℃.
7. The preparation method according to claim 2, characterized in that, In step C), the calcination time is 0.3~0.7h.
8. The preparation method according to claim 2, characterized in that, In step C), after calcination, the process further includes: acid washing; The pickling includes: ultrasonic dispersion washing with acid solution; The acid solution includes hydrochloric acid solution or sulfuric acid solution; The process after acid washing also includes: filtration and drying.
9. The application of the high-entropy alloy oxide according to claim 1 or the high-entropy alloy oxide prepared by any one of claims 2 to 8 as an anode catalyst for proton exchange membrane water electrolysis.
Citation Information
Patent Citations
Preparation method of high-entropy metal oxide FeCoNiCrMnOx
CN114807998A
Non-noble metal based electro-catalyst compositions for proton exchange membrane based water electrolysis and methods of making
US20170233879A1